GERAKAN DAKWAH DALAM UPAYA PENCEGAHAN DINI TERHADAP PENYEBARAN DAN PENERIMAAN ISLAMISME KELOMPOK RADIKAL- TERORISME DI LAMPUNG - Syukur, Abdul (Analisis: Jurnal Studi Keislaman, 2015)
DA’WAH  AS  THE  EARLY  PREVENTION  EFFORTS AGAINST THE SPREAD AND ACCEPTANCE OF ISLAMISM IN RADICAL TERRORISM  IN LAMPUNG:  This paper is set out from the anxiety if the anarchism in term of acceptance  and the spread of Moslem which is done by certain  group of salafi in Lampung as the response of the democracy process after reformation era in order to face the political ideology that is pro- democracy and contra with democracy. With a practical analysis, the  authors  found  that  the  construction  of narrative  Islamism developed by radical groups in society Lampung only radical Moslem didn’t lead to radicalism and terrorism. The number of the radical group is small. The narratives Islamism spread by radical groups  with  different  patterns  of deployment  and  distribution factors by which identifying  and facilitating the transmission  of Islamism is generally not accepted by the majority of the Islamic community in Lampung. Most of Lampung people lead the moderate Islamic and cultural Lampung Piil Pesanggiri  and Adat Muakhi which are rejected the terrorism.